The role of polymorphism in TNF gene promotive area in the development of chronic obstructive pulmonary disease - G. N. Seitova; Ye. B. Bukreeva; S. V. Buykin; O. Yu. Bychkova; Ye. A. Dementyeva; S. V. Nesterovich; V. P. Puzyryov (Бюллетень сибирской медицины)
Association of –308G/A-polymorphism of α-tumor necrosis factor (TNF) gene with the development of chronic obstructive pulmonary disease has been investigated in two populations of Tomsk city (Siberian Tatars and Russians). As a result, it has not been marked any genotype distribution deviation of expected in patient groups as well as in control groups at Hardy-Vainberg equilibrium. Statistically significant difference in allele distribution rate at patients with COPD and in control groups has not been found (p > 0,5) including ethnic groups (Russians and Tatars). Differences in genotype distribution at patients and control group have been found for Tatars due to heterosive carrier (AG) prevalence at patients (p < 0,05). The obtained data allow to conclude the presence of association of –308G/A-polymorphism of TNF gene with the COPD development at Siberian Tatars.